2017
DOI: 10.1038/s41564-017-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

Gut-homing Δ42PD1+Vδ2 T cells promote innate mucosal damage via TLR4 during acute HIV type 1 infection

Abstract: The innate immune cells underlying mucosal inflammatory responses and damage during acute HIV-1 infection remain incompletely understood. Here, we report a Vδ2 subset of gut-homing γδ T cells with significantly upregulated Δ42PD1 (a PD1 isoform) in acute (~20%) HIV-1 patients compared to chronic HIV-1 patients (~11%) and healthy controls (~2%). The frequency of Δ42PD1Vδ2 cells correlates positively with plasma levels of pro-inflammatory cytokines and fatty-acid-binding protein before detectable lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Intriguingly, these effects were again associated with a shift in cytokine production by pulmonary αβ T-cells, further suggesting that γδ T-cells can exert complex effects via their influence on other mucosal leukocyte populations. Indeed, gut-tropic γδ T-cells can promote Th1/Th17 differentiation of CD4 + T-cells in vivo to exacerbate colitis in murine models ( 48 , 49 ), and a Vδ2 + subset expressing the PD1 isoform Δ42 promotes gut inflammation in humanized mice via putative effects on DC ( 50 ). Together, these data suggest that γδ T-cells may exert similarly potent influences on adaptive immunity and inflammation in human mucosal tissues.…”
Section: γδ T-cells Mediate Epithelial Barrier Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, these effects were again associated with a shift in cytokine production by pulmonary αβ T-cells, further suggesting that γδ T-cells can exert complex effects via their influence on other mucosal leukocyte populations. Indeed, gut-tropic γδ T-cells can promote Th1/Th17 differentiation of CD4 + T-cells in vivo to exacerbate colitis in murine models ( 48 , 49 ), and a Vδ2 + subset expressing the PD1 isoform Δ42 promotes gut inflammation in humanized mice via putative effects on DC ( 50 ). Together, these data suggest that γδ T-cells may exert similarly potent influences on adaptive immunity and inflammation in human mucosal tissues.…”
Section: γδ T-cells Mediate Epithelial Barrier Protectionmentioning
confidence: 99%
“…Indeed, Vδ2 + T-cells are capable of expanding yet further to dominate the blood lymphocyte pool in a wide range of infections ( 52 , 53 ), which has led to extensive study of these cells in the circulation as well as the common misconception that they are restricted to the blood. However, several reports have now identified that the majority of blood Vδ2 + T-cells express homing receptors for epithelial barrier sites including the skin (CLA) and intestine (integrin α4β7 and CCR9) ( 50 , 54 , 55 ). This tissue-tropic phenotype is consistent with the role of Vδ2 + T-cells in host protection against pathogens that colonize epithelial barriers and produce the metabolite ( E )-4-hydroxy-3-methyl-but-2-enyl pyrophosphate (HMB-PP) ( 56 ).…”
Section: γδ T-cells Stimulate Complex Mucosal Leukocyte Responsesmentioning
confidence: 99%
“…Under baseline conditions, TLR4 is expressed at low levels in the brain, including the hypothalamus of rodents; however, its expression increases considerably when rodents are fed a HFD ( Milanski et al, 2009 ). In other brain regions, TLR4 expression is involved in medical conditions such as autoimmunity ( Kerfoot et al, 2004 ), HIV infection ( Cheung et al, 2017 ) and Alzheimer’s disease ( Ledo et al, 2016 ), illustrating its pleiotropic roles in brain immunity and defense. A detailed screening of dietary fats that could potentially promote the activation of hypothalamic TLR4 identified long-chain SFAs as the most potent inducers of its association with MyD88, resulting in the activation of NF-κB and JNK and leading to endoplasmic reticulum stress ( Zhang et al, 2008 ).…”
Section: Mechanisms Of Hypothalamic Microglia Activation In Obesitymentioning
confidence: 99%
“…Interestingly, Sooty mangabeys, which are innately resistant to SIV disease, encode a truncated variant of TLR4 that is less responsive to in vitro stimulation [68]. Intestinal pathogenesis during HIV infection may also be mediated by a Vδ2 subset of gut-homing γδ T cells with significantly upregulated ∆42PD1 -a PD1 isoform that can also act as a ligand for TLR4 [69]. Consistent with this hypothesis, HIV-infected individuals have been demonstrated to have elevated levels of these cells, and adoptive transfer of these cells into humanized mice caused inflammatory damage that could be prevented by TLR4 blockade [69].…”
Section: Tlr4mentioning
confidence: 99%